Post-War Revitalization of Ukrainian Agriculture: Lessons from South Korea’s Rural Development Model - Stanislav Rieznik; Hwan-Beom Lee (Transylvanian Review of Administrative Sciences, 2025)
Ukraine’s agricultural sector has been devastated by war, exposing systemic challenges faced by small-scale farmers, including inadequate infrastructure, limited credit access, and underdeveloped cooperatives. This study explores lessons from South Korea’s post-war agricultural transformation, emphasizing sustainable governance, cooperative development, and community-driven initiatives. Using a mixed-methods approach, the research combines historical analysis with expert interviews from Ukraine and South Korea to contextualize applicable strategies. South Korea’s Saemaul Undong and National Agricultural Cooperative Federation provide a blueprint for fostering resilience, productivity, and inclusivity. Key recommendations include strengthening local governance through Ukraine’s decentralization reforms, empowering smallholder farmers via cooperatives, and investing in infrastructure to reduce post-harvest losses. By integrating top-down policy guidance with bottom-up community engagement, Ukraine can adapt these proven strategies to its unique socio-political context, fostering sustainable recovery and resilience in its rural economy.